Dynamic Architecture of Eukaryotic DNA Replication Forks In Vivo, Visualized by Electron Microscopy - Zellweger, Ralph; Lopes, Massimo (Methods in molecular biology (Clifton, N.J.), 2018)
The DNA replication process can be heavily perturbed by several different conditions of genotoxic stress, particularly relevant for cancer onset and therapy. The combination of psoralen crosslinking and electron microscopy has proven instrumental to reveal the fine architecture of in vivo DNA replication intermediates and to uncover their remodeling upon specific conditions of genotoxic stress. The replication structures are stabilized in vivo (by psoralen crosslinking) prior to extraction and enrichment procedures, allowing their visualization at the transmission electron microscope. This chapter outlines the procedures required to visualize and interpret in vivo replication intermediates of eukaryotic genomic DNA, and includes an improved method for enrichment of replication intermediates, compared to previously used BND-cellulose columns.